RELIGIOSITY, IMAGINATION AND TED HUGHES: HIS EARLY POETRY AND THE ROMANTICS - Dhariwal, Jaibir; Parashar, Rajbir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In his early poetry, Ted Hughes is anxious to make an exit out of industrial imagery of his times. His use of animal imagery purports to inculcate a reverence for the otherness of the various living beings existing outside and independent of the human world. Like the Romantics, this inheres a strategy to compensate the lost life of ‘imagination and emotion’ modern world has suffered towards the close of the twentieth century. This abundance of animal imagery is an inverted dialogue with the simple and easily connectable forms of Nature. In Hughes’s early poetry, poetic personae or narrators are basically located in highly industrialized cultural contexts, having ‘hole in the head’. In place of rationalist humanism and instrumental rationality, Ted Hughes posits imagination itself as a distinct source of spiritual experience, a sort of foundation of religiosity in later part of 20 th century. In order to re-establish its due place in the human ecology, it requires reliable tools to expose and discredit the rigidly ‘egocentric’ tendencies of the civilized modern man. His early poetry is an example of this part of his vision where poetry becomes a spiritual and healing practice for the poet as well as the reader. Even multiple critical approaches to his poetry, appreciative or more critical of his worldview, all undeniably acknowledge this underlying centrality of poetry as spiritual linguistic endeavour of the poet. This aspect of his poetry brings him close to some of the prominent Romantic poets in British literature.